A field emission performance test device for continuous adjustment of the electrode spacing in the vacuum system. (14th December 2018) - Wu, Linling; Pei, Xiaoqiang; Cheng, Yongjun; Sun, Wenjun; Wang, Yongjun; Dong, Meng; Xi, Zhenhua; Sun, Jian
Abstract: This work presents a device that can adjust electrode spacing inside a vacuum system to evaluate the field emission characteristics of a carbon nanotube array cathode grown on a stainless steel (SS) substrate. It was made by coaxial connection of the rear end of a screw micrometer, which acts as the anode, with a stepper motor. The distance between the anode and the cathode was controlled by altering the pitch of the stepper motor with an angle precision of 1 degree. Therefore, the electrode separation can be tuned in the range of 0–15 mm at 1.388 µm incremental steps. Compared with devices with a fixed electrode spacing, the advantage is that this device allows continuous regulation of the electrode spacing after it is placed in a vacuum system to test the emission properties under various electrical parameters in one process, thus avoiding repeated breaking of the vacuum environment. Therefore, test efficiency is improved, hence saving manpower, material resources, testing time and greatly reducing the cost of experimentation. This device is simple in structure and relatively easy to prepare.